Physical Modelling on Detecting Buried Object Using Electrical Resistivity Imaging (ERI). Issue 1 (July 2016) - Hazreek, Z A M; Nizam, Z M; Azhar, A T S; Aziman, M; Shaylinda, M Z N
Abstract: This study focused on the evaluation of electrical resistivity method (ERM) for buried object detection and its relationship due to the different stiffness of material. In the past, the conventional method to detect the buried structure was face some limitation due to the time and cost. For example, previous approach related to the trial and error excavation has always expose to some risky outcome due to the uncertainties of the buried object location. Hence, this study introduced an alternative technique with particular reference to resistivity method to detect and evaluate the buried object with different strength of stiffness. The experiment was performed based on field miniature model (small scale study) using soil trial embankment made by lateritic soil and various concrete cube strengths (grade 20, 25 and 30) representing buried object with different conditions. 2D electrical resistivity test (electrical resistivity imaging) was perform using ABEM Terrameter SAS4000 during the data acquisition while the raw data was process using RES2DINV software. It was found that the electrical resistivity method was able to detect the buried concrete structures targeted based on the contrast of the electrical resistivity image produced. Moreover, three different strength of concrete cube were able to be differentiated based on the electrical resistivity values (ERV) obtained. This study found that the ERV of concrete cube for grade 20, 25 and 30 were 170 Ωm, 227 Ωm and 503 Ωm, respectively. Hence, this study shows that the ERV has a strong relationship with different stiffness of material thus applicable to be a useful alternative tool in underground structure detection.